Young adults' fear of disasters: A case study of residents from Turkey, Serbia and Macedonia. (April 2019) - Cvetković, Vladimir M.; Öcal, Adem; Ivanov, Aleksandar
Abstract: This paper presents the results of quantitative research regarding the level and the causes of fear of disasters among young adults in Turkey, Serbia, and Macedonia. The survey was conducted using a questionnaire that was given and then collected hand by hand that explored in depth the disaster-related fears among 537 respondents during 2016. The questionnaire explored students' basic demographics and their level of fear, as well as the causes and sources of fear. Across the three countries, the results indicated an excessive level of fear both of earthquakes and of epidemics. In addition, participants reported that they were particularly afraid for their personal lives and, to a greater extent, for the health of their parents. Experiences with bad weather conditions, pictures of the consequences of disasters, and past disaster experience were found to exacerbate fear. It was also found that females were more afraid, with a possible socio-cultural-laden link to an ethos of protection versus participation. Findings can be used to create focused strategies at a national level intended to reduce excess fear of disasters and facilitate a more prepared public through policy and education programme development.